A forma????o dos enfermeiros para o sistema ??nico de sa??de: pr??-sa??de como estrat??gia de mudan??a - Leite, Graciene Lannes (2016)
This study questions the nurses training process for the Sistema Unico de Saude (SUS), Unified Health System. In recent years, education and health orientation of vocational training in health and its academic and practical aspects of work with the aim of adapting these to the demands of the SUS have been under discussion. To this end, The National Orientation Program for Professional Training in Health (Pro-Health) and The Program of Education for Work (PET-Health) were established. With the aim of analyzing the implementation processes of these programs in the undergraduate Nursing course, a public higher education institution in S??o Paulo was chosen as the locus for empirical research. For this purpose, it was necessary to conduct a study on the public policies of undergraduate level training of health care professionals in Brazil, with greater attention to the two mentioned programs. The theoretical reference is set in the work of Goodson, Aplle and Bernstein, which discusses education and curriculum; the professional experience of the author in the implementation of these programs in another IES (HEI) was useful in the construction of this framework. The research, of qualitative nature and exploratory character, used methodological and analytical contribution through research of legislation and documentation focusing on the training of nurses, from the perspective of the Policy cycle approach, by Ball and colleagues, which provides the contexts of influence, for text production and practice. The approach of the context of influence and text production was carried out from an analysis of the National Curriculum Guidelines for Undergraduate Nursing Courses (DCN / ENF) and Pro-Health Handbook. The context data of practice were collected through semi-structured interviews with teachers, supervisors and former students of the undergraduate course in Nursing. The content analysis technique was used which considered the topic as the unit of analysis for organizing and interpreting the answers of the interviewees. The triangulation undertaken as a research strategy for data collection combination allowed a full view of the different contexts that involve discussions of Education and Health and the orientation of academic training and work practice of nurses. The results revealed the potential of the pedagogical proposal of the Pro / PET-Health as an important mechanism for school integration - health care - community, through the production of knowledge based on the demands of the SUS and the performance of students in actual practice scenarios toward the new training mandate. Furthermore, it was observed that the concreteness of this potential is still a great challenge to the implementation, monitoring and evaluation that ensure the adequacy and continuity of the orientation of nursing education policies. Finally, by combining the results with the framework of the policy cycle approach, it was concluded that the subjects of this training process should seek cooperation with others, favoring the connection with policy makers and other social institutions, in the pursuit of achievement of transforming education, making choices and allowing memberships that give legitimacy and consequent "feedback" on the management of public education.